(untitled) (International Journal of Environmental Sciences, 2025)
There were 178 million new fractures worldwide in 2019 (up 33.4% from 1990). Many people suffer broken bones each year due to accidents and illnesses. In the majority of these cases, external treatments are not enough to repair the fractures, so non-biodegradable implants such as cobalt based alloys, titanium alloys are used to repair the fractures. The biological behaviour of these implants has been observed to be superior to that of the conventional implants. However, they must be removed from the human body once the bone healing process is completed. In this project, a fractured femur is modelled with a biodegradable implant and the stress, strain, and total deformation distributions of two biodegradable materials (Mg and Zn alloys) are compared using ANSYS Workbench environment.